INFORMATIVE-COMMUNICATION TECHNOLOGIES AS MEAN OF FORMING OF THE SELF-EDUCATIONAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS (Journal of Information Technologies in Education (ITE), 2013)
The article opens the question of the use of informative-communicative technologies in process of formation of the selfeducational competence in teachers of primary school.
Keywords: informatively communication technologies; informative-communication pedagogical environment